Ochrona godności osoby skazanej w prawie karnym wykonawczym. Wybrane aspekty - Bielecki, Marek (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The subject of the present study is the preservation of the dignity of sentenced person in executive penal law. The main purpose is the answer to the question, if penal law preserves this value in adequate measure? The author undertakes the analysis of the issue in such approach, which so far now has not been developed in the literature on the subject. The suggested systematics is based on the hierarchy of needs of the American philosopher Abraham Maslow. The author assigns individual guarantees in the field of religious freedom to the needs of lower and higher order.